Utility of interventional endoscopic ultrasound in pancreatic cancer - On, Wei; Ahmed, Wafaa; Everett, Simon; Huggett, Matthew; Paranandi, Bharat (Frontiers in Oncology, 2023)
Endoscopic ultrasound (EUS) has an important role in the management algorithm of patients with pancreatic ductal adenocarcinoma (PDAC), typically for its diagnostic utilities. The past two decades have seen a rapid expansion of the therapeutic capabilities of EUS.Interventional EUS is now one of the more exciting developments within the field of endoscopy. The local effects of PDAC tend to be in anatomical areas which are difficult to target and endoscopy has cemented itself as a key role in managing the clinical sequelae of PDAC. Interventional EUS is increasingly utilized in situations whereby conventional endoscopy is either impossible to perform or unsuccessful. It also adds a different dimension to the host of oncological and surgical treatments for patients with PDAC. In this review, we aim to summarize the various ways in which interventional EUS could benefit patients with PDAC and aim to provide a balanced commentary on the current evidence of interventional EUS in the literature.